The Needs for Psycho Spiritual Competencies for Disaster Workers in Malaysia - Khatijah Othman; Nik Nadian Nisa Nik Nazli; Nor Adila Syahira Jusoh; Nurhafizah Mohd. Sukor; Suhailiza Md. Hamdani; Muhammad Khairi Mahyuddin; Yuseri Ahmad; Marina Munira Abdul Mutalib; Mashitah Sulaiman (Universiti Sains Islam Malaysia, 2024)
Vol. 22 No. 2 (2020): Journal of Islamic Social Sciences and Humanities (Special Issue)